Iatrogenic Severe Hypernatremia: A Case Report - Hala H. Mosli, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Lactulose is a common first-line therapy for acute and chronic hepatic encephalopathy, which is generally considered a safe medication and used liberally. This report aims to highlight an uncommon but serious side effect of using lactulose. A case study is presented of a severe and acute hypernatremia caused by lactulose therapy for acute hepatic encephalopathy precipitated by a transjugular intrahepatic portosystemic shunt procedure.